Design and analysis of flux-switching permanent magnet motor with parameters optimization - Mo,Ke (Nanyang Technological University, 2020)
This paper discussed the design and optimization process of a flux-switching permanent magnet motor, the flux switching permanent magnet motor has been regarded as a highly reliable machine with both armature windings and magnets on the stator. Due to the high torque production capacity with reasonable low torque ripple, FSPM motors with high phase numbers are widely used for powertrain applications of hybrid electric vehicles. However, the performance of the FSPM motors highly depends on the structure features of the machine, it is necessary to find optimal values for the parameters to achieve the highest efficiency for the motor. This paper first introduces the background and research status of flux switching motor. Then, taking the 12/10 pole flux switching permanent magnet motor as an example, its structure and working principle are introduced in detail. The cogging torque of the flux-switched permanent magnet motor occupies a dominant position in the torque ripple with its unique double salient pole structure and high air gap magnetic flux density. The simulation results indicate that changing some parameters reasonably can reduce the cogging torque at the cost of little output torque loss which improve the performance of motor effectively.